THE POLITIZATION OF PAVEL FLORENSKY’S EXPECTED POLITY IN THE FUTURE: FROM “CORRECT READING” TO “TODAYIZATION” - Dusevičius, Vidas (Politologija, 2017)
The article deals with the interpretations of Pavel Florensky’s Expected Polity in the Future (1993) in Russian contemporary conservative intellectual groups (Zavtra, Izborsk Club, Alexander Prokhanov, Alexander Dugin and the people around him). Neither Dugin nor Prokhanov commented on, evaluated or interpreted Florensky’s Expected Polity in the Future. Dugin is more inclined to associate Florensky with the context of Russia as representing the platonic tradition of philosophy. The polemic of Vitaly Averyanov, Deputy Chairman of the Izborsk Club, who questions the attribution of Florensky to the representatives of conservatism is also mentioned. Attention is focused on the people around Dugin, the majority of whom are to be related to the website ruskline.ru. This group highlights and supports the role of Florensky as a philosopher who represented the conservative trend. Emphasis is put on the applicability and fitting of Florensky’s ideas (postulation of Russia’s self-isolation, cutting itself off from the West, criticism of representative democracy, a strong state and a single-person rule) in today’s Russia. Also, the personal example of Florensky as a model of the coherence of orthodox spirituality and patriotism is emphasized. In the interpretations of the Expected Polity in the Future, certain repercussions of polemic in the groups of the conservative mind on the Tsarist Russia, Soviet Union and present-day Russia as a continuer of the empire (empires) have been noticed. The authors of this article uphold the view that the interpretations of Expected Polity in the Future often are characterized by “correct reading”, “todayization” – certain preconceived criteria for the evaluation and selection of the philosophical mind in Russian contemporary conservative intellectual groups. The abovementioned elements of the interpretations of Florensky’s Expected Polity in the Future reflect far broader trends of the modern Russian conservative mind, as a field of the search for ideology, in which such thinkers as Ivan Ilyin and Nikolai Berdyaev are involved.